Monarch butterfly population decline in North America: identifying the threatening processes. Issue 9 (20th September 2017) - Thogmartin, Wayne E.; Wiederholt, Ruscena; Oberhauser, Karen; Drum, Ryan G.; Diffendorfer, Jay E.; Altizer, Sonia; Taylor, Orley R.; Pleasants, John; Semmens, Darius; Semmens, Brice; Erickson, Richard; Libby, Kaitlin; et al.
Abstract : The monarch butterfly ( Danaus plexippus ) population in North America has sharply declined over the last two decades. Despite rising concern over the monarch butterfly's status, no comprehensive study of the factors driving this decline has been conducted. Using partial least-squares regressions and time-series analysis, we investigated climatic and habitat-related factors influencing monarch population size from 1993 to 2014. Potential threats included climatic factors, habitat loss (milkweed and overwinter forest), disease and agricultural insecticide use (neonicotinoids). While climatic factors, principally breeding season temperature, were important determinants of annual variation in abundance, our results indicated strong negative relationships between population size and habitat loss variables, principally glyphosate use, but also weaker negative effects from the loss of overwinter forest and breeding season use of neonicotinoids. Further declines in population size because of glyphosate application are not expected. Thus, if remaining threats to habitat are mitigated we expect climate-induced stochastic variation of the eastern migratory population of monarch butterfly around a relatively stationary population size.